Fallen - Kate, Lauren (New York : Delacorte Press, 2009)
Suspected in the death of her boyfriend, seventeen-year-old Luce is sent to a Savannah, Georgia, reform school where she meets two intriguing boys and learns the truth about the strange shadows that have always haunted her.
Young Adult
Young Adult.
830
Keywords: Supernatural -- Juvenile fiction; Reformatories -- Juvenile fiction; Schools -- Juvenile fiction; Reincarnation -- Juvenile fiction; Angels -- Juvenile fiction; Savannah (Ga.) -- Juvenile fiction; Supernatural -- Fiction; Reformatories -- Fiction; Schools -- Fiction; Love -- Fiction; Reincarnation -- Fiction; Angels -- Fiction; Savannah (Ga.) -- Fiction; Supernatural -- Fiction; Reformatories -- Fiction; School stories; Love stories; Reincarnation -- Fiction; Angels -- Fiction; Savannah (Ga.) -- Fiction; Love stories